Environmental Signals Generate a Differential and Coordinated Expression of the Heme Receptor Gene Family of Bartonella quintana - Battisti, James M. (American Society for Microbiology, 2006)
Of all bacteria, Bartonella quintana has the highest reported in vitro hemin requirement, yet an explanation for this remains elusive. To produce diseases such as trench fever, endocarditis, and bacillary angiomatosis, B. quintana must survive and replicate in the disparate environments of the Pediculus humanus corporis (body louse) gut and the human vasculature. We previously identified a five-member family of hemin binding proteins (Hbps) synthesized by B. quintana that bind hemin on the outer surface but share no similarity to known bacterial heme receptors. In the present study, we examine the transcription, regulation, and synthesis of this virulence factor family by cultivation of the bacterium in environments that simulate natural heme, oxygen, and temperature conditions encountered in the host and insect vector. First, quantitative real-time PCR data show that hbpC expression is regulated by temperature, where a >100-fold increase in transcript quantity was seen at 30°C relative to 37°C, suggesting that HbpC synthesis would be greatest in the cooler temperature of the louse. Second, cultivation at human bloodstream oxygen concentration (5% relative to 21% atmospheric) significantly decreases the transcript quantity of all hbp genes, indicating that expression is influenced by O(2) and/or reactive oxygen species. Third, a differential expression pattern within the hbp family is revealed when B. quintana is grown in a range of hemin concentrations: subgroup I (hbpC and hbpB) predominates in a simulated louse environment (high heme), and subgroup II (hbpA, hbpD, and hbpE) is preferentially expressed in a simulated human background (low heme). By using two-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis, immunoblotting, and matrix-assisted laser desorption ionization—time of flight mass spectrometry fingerprinting, we demonstrate that synthesis of HbpA correlates with hbpA transcript increases observed at low hemin concentrations. Finally, an hbpA promoter-lacZ reporter construct in B. quintana demonstrates that a transcriptional regulator(s) is controlling the expression of hbpA through a cis-acting regulatory element located in the hbpA promoter region.